Liver disease symptoms are associated with higher risk of adverse clinical outcomes: A longitudinal study of North American adults with chronic Hepatitis B. Issue 3 (11th May 2021) - Evon, Donna M.; Lin, Hsing‐Hua S.; Fontana, Robert J.; Khalili, Mandana; Yim, Colina; Wahed, Abdus S.; Hoofnagle, Jay H.; ,
Summary: Background: Symptoms of chronic hepatitis B (CHB) are not well characterised. Aims: To evaluate CHB symptoms and associations with disease activity and clinical outcomes. Methods: Longitudinal data from 1576 participants in the Hepatitis B Research Network Cohort Study who completed symptom assessments were analysed. A composite symptom score was calculated using a Symptom Checklist (0 = none to 40 = extreme). Multivariable mixed models assessed variables associated with symptom change over time. Latent class symptom trajectories were evaluated. The cumulative probability of long‐term clinical outcomes (new onset cirrhosis, hepatic decompensation, hepatocellular carcinoma, liver transplantation, death) was examined by baseline symptom groups. Results: Participants median age was 42 (range: 18‐80), 51% were male, 75% Asian, (68% of whom were born outside North America) with a median follow‐up of 4.2 years. On average, symptoms did not significantly change over time. The multivariable model identified several variables associated with higher symptoms during follow‐up: being female, non‐Asian, born in the United States/Canada, lower education, higher AST, lower platelets and more comorbidities. Two patient subgroups were identified based on longitudinal symptom trajectories: a low symptom group (92%, n = 1451) with symptom scores averaging 2.4 over time and a moderate symptom group (8%, n = 125) with symptom scores averaging 11.5. During follow‐up, 7.3% in the moderate symptom group, but only 3.2% of the low symptom group, developed adverse outcomes ( P = 0.02). Conclusions: In this large cohort of CHB patients, symptoms were generally mild and stable over time. However, in some patients with moderate symptoms at baseline, deleterious clinical outcomes were more frequent at follow‐up. ClinicalTrials.gov Identifier: NCT01263587.